Short Communication: Lugol’s iodine test on Rafflesia patma–Tetrastigma leucostaphylum intersection tissue for preliminary starch visualization - Adhityo Wicaksono; Sofi Mursidawati (Smujo International, 2020)
Abstract. Wicaksono A, Mursidawati S. 2020. Short Communication: Lugol’s iodine test on Rafflesia patma-Tetrastigma leucostaphylum intersection tissue for preliminary starch visualization. Nusantara Bioscience 12: 91-96. As holoparasitic plant, Rafflesia has no recognizable plastid genome, but it has plastid-like organelle. Despite the fact that it obtains nutrients from host plant, it is unknown if Rafflesia stores primary metabolites, such as carbohydrates, from its host. A study was performed to visualize the starch in Rafflesia patma Blume proximal tissue which was intersected to its host root, Tetrastigma leucostaphylum (Dennst.) Alston, using modified Sachs’ test with Lugol’s iodine. The result revealed the absence of blackening in the R. patma tissue caused by starch reaction with the iodine, but occurred in the root cortical tissue of T. leucostaphylum. The absence of starch in R. patma tissue indicated that possibly the plastid-like organ has no similar function to amyloplast, and starch is not used for storage in the flower. It is likely that R. patma relies completely on the host’s photosynthate to maintain the flower metabolism during anthesis period. However, detailed histochemical analysis for starch or carbohydrate is needed for confirmation whether the starch is existing even in small quantity, and molecular genetic observation on sucrose intake and flowering (anthesis) regulatory genes will also be required to confirm if Rafflesia takes the photosynthate directly from its host and possibility if Rafflesia coordinates the formation of flower bud and anthesis between the endophytic tissues to prevent overexploitation of nutrients from its host.